INOVASI “LAPORRAMA” DALAM PELAYANAN PUBLIK DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SINTANG - Eka Apriyani; Arya Eka Wijaya; Dimas Rahma Pratama; Sari Fipriyanti (Universitas Hamzanwadi, 2024)
This research examines the implementation of LAPORRAMA, an innovative digital system introduced by the Disdukcapil of Sintang Regency, aimed at enhancing public satisfaction in civil registration services, particularly for birth and death certificates. The study investigates key issues such as accessibility, data accuracy, and transparency in service delivery within rural areas, where geographical challenges hinder access to essential documentation. Employing qualitative methods, including interviews with key stakeholders such as health officials and community leaders, the findings reveal that LAPORRAMA significantly streamlines administrative processes, reducing the time and effort required for obtaining vital records. Notably, the integration of this system facilitates immediate issuance of birth certificates at local health facilities, improving user experiences and mitigating the bureaucratic burdens associated with traditional manual processes. Additionally, LAPORRAMA addresses issues of corruption by ensuring transparency in administrative fees. Overall, the research highlights LAPORRAMA's critical role in enhancing the quality of public services and fostering trust in government institutions, thereby contributing positively to community well-being in Sintang Regency.